An enigmatic new octocoral species (Anthozoa, Octocorallia, Malacalcyonacea) from Isla del Coco National Park - Breedy Shadid, Odalisca (2023)
Aliena parva gen. et sp. nov. is described from Cocos Island, Costa Rica. The species was found at various islets and rocky outcrops north and northwest of the island, 20–30 m in depth. The genus is characterised by polyps, retracting into calyces, that form thin encrusting mats extending on dead or live substrates. Sclerites are mostly asymmetrical spindles. Anthocodial rods are arranged in points, not forming a collaret. Colonies and coenenchymal sclerites are red, and polyps are transparent. Using an integrative taxonomic approach, we found the new genus to morphologically and genetically differ from all other described taxa. The molecular phylogenetic analyses provide strong support for the placement of this new genus in the family Pterogorgiidae. Morphologically it is unlike any of the other members of this family, necessitating an amendment to the diagnosis of Pterogorgiidae. Like several other known taxa of octocorals with encrusting growth forms, Aliena gen. nov. appears to have evolved from a gorgonian ancestor by loss of an internal skeletal axis. It is the first member of Pterogorgiidae to be reported from the eastern Pacific, contributing further to the knowledge of marine biodiversity in the eastern tropical Pacific and to the octocoral biodiversity of Cocos Island in particular.